Data Logger berbasis IC Multiplexer untuk Pengukuran Arus dan Tegangan pada Panel Surya Skala Besar - Ali Basrah Pulungan; Siti Rahmadhani Putri (Universitas Negeri Padang, 2022)
Parameters of large-scale solar panels can be measured directly and automatically using a data logger system. The input data from the data logger can be optimized by using the analog input on the multiplexer IC to improve the performance of recording parameter data on large-scale solar panels. This data logger system consists of an Arduino Uno microcontroller as the central control, which is equipped with a current sensor, voltage sensor, RTC DS3231, multiplexer IC, and SD card module. The data obtained in real-time every 5 minutes will be stored on the SD card in the form of a txt file with the format of the day, date, time, voltage value, and current value on each solar panel. The results of this test will show that the solar panel measurement data using a data logger with multiplexer ICs will be able to store and display large amounts of data on the panel.